Rebreather divers’ responses to hyperalkaline hydroxide ingestion and aspiration (‘caustic cocktail’) events - Dong, Grant; Rhiannon, Brenner; Buzzacott, Peter; Tillmans, Frauke (Undersea and Hyperbaric Medical Society, 2022)
Introduction/Background: Rebreathers recycle exhaled air using soda-lime scrubber material to remove carbon-dioxide and injecting oxygen into the normally closed breathing loop. When water enters the system, it generates a hyperalkaline hydroxide solution, commonly known as a “caustic cocktail”. Unexpectedly ingesting this can potentially result in serious harm. The gold standard first-aid treatment for hyperalkaline ingestion is to flush the mouth with water. This study surveyed caustic cocktail experiences of rebreather divers.